Silver embedded nanostars for SERS with internal reference (SENSIR)1. Issue 28 (28th July 2015) - Fales, Andrew M.; Vo-Dinh, Tuan
<x xml:space="preserve">Abstract</x> Reference dye labeled nanostars are embedded in a partial silver shell, retaining the sharp gold tips for non-aggregated SERS of external analytes while providing an internal reference signal.